1984
DOI: 10.1577/1548-8659(1984)113<205:mshars>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Muskellunge Spawning Habitat and Reproductive Success

Abstract: Reproduction of muskellunge Esox masquinongy has failed in many waters that formerly supported self‐sustaining populations. Laboratory experiments were conducted to isolate causes of such failures. Differential mortality occurred among lots of muskellunge eggs incubated in jars of unaceated lake water over substrates of sand, gravel, silt, aquatic macrophytes, wood, tree leaves, polyethylene screen, and bare glass. High and rapid early mortality (days 1–2), attributable to low dissolved oxygen (DO) concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 0 publications
1
72
1
Order By: Relevance
“…Muskellunge may benefit from decreased water levels over winter, as previous studies have suggested that self-sustaining muskellunge populations and high-hatching success are related to winter drawdown (Dombeck et al 1984;Zorn et al 1998). The drawdown period is believed to result in substrate aeration and organic material desiccation, forming a firmer substrate that may improve muskellunge spawning habitat (Dombeck 1986).…”
Section: Resultsmentioning
confidence: 99%
“…Muskellunge may benefit from decreased water levels over winter, as previous studies have suggested that self-sustaining muskellunge populations and high-hatching success are related to winter drawdown (Dombeck et al 1984;Zorn et al 1998). The drawdown period is believed to result in substrate aeration and organic material desiccation, forming a firmer substrate that may improve muskellunge spawning habitat (Dombeck 1986).…”
Section: Resultsmentioning
confidence: 99%
“…Natural viability rates could serve as an indicator of spawning habitat quality in terms of environmental conditions such as water temperature and dissolved oxygen concentrations. Dombeck (1984) and Zorn et al (1998) demonstrated how low dissolved-oxygen levels at the spawning substrate-water interface could cause widespread egg losses. Natural coastal wetland processes and biochemical pathways affecting DO microstratification, and the effects of localized eutrophication and flow interruption, are a potential major detriment to muskellunge habitat quality.…”
Section: Identification and Characterization Of Spawning And Nursery mentioning
confidence: 99%
“…Offshore spawning in Lake St. Clair and Leech Lake was different than the shoreline spawning commonly described by Crossman (1990) and others. Dombeck et al (1984) found muskellunge spawning areas in seven Wisconsin and Michigan lakes that were located in shallows near shore (mean depth of the spawning sites was 74 cm). Zorn et al (1998) described muskellunge spawning habitat in four Wisconsin lakes as occurring in shallow ( < 1 m) bays over mucky bottoms covered with dead vegetation.…”
Section: Discussionmentioning
confidence: 99%
“…Populations of muskellunge Esox masquinongy and northern pike Esox lucius are sensitive to shoreline and related land development that removes vegetation, reduces water quality, and adds biological oxygen demand to sediments (Brynildson 1958;Dombeck et al 1984). Eutrophication affects muskellunge eggs and larvae that are intolerant of low dissolved oxygen concentrations in a microzone along the bottom where they are dispersed (Dombeck et al 1984).…”
Section: Introductionmentioning
confidence: 99%